(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
It has become satisfactorily convincing that the reformation and development of Egyptian education are inevitable. Education, in Egypt, has become one of the most rudimentary causes as it is the real and only beginning for any type of progress in all walks of life. Advanced countries, as has been affirmed by contemporary history, have started their progress from the gate of education. These countries always give education all the priorities in their policies, programs and strategies. Efforts to reform and develop education in Egypt took various forms: Holding conferences, meetings, issuing documents and inventing strategies, etc. However, there are still many defects and gaps that need to be filled. These shortcomings actually impede the process of the reformation and development of education. Therefore, it has become an obligation to reconsider the policies and strategies of that system as an inevitable step to develop and promote it. To achieve the objectives of promoting the educational system in Egypt by creating a competent graduate, the study sought the experiences of some foreign advanced countries. The descriptive approach has been used in this study to treat the data on a critical and analytical basis. The researcher has reached a number of important conclusions and lessons. Experiences of the advanced countries in the field of education clearly indicate that: 1-The minister of education should not be the only person to demarcate the educational policy; 2- education should be given a comprehensive outlook; 3- human and financial potentials should be always available; 4- societal participation and contribution by the experts, teachers, consultants, and administrative offices should be guaranteed. Accordingly, the educational policy will surely be entrusted to those who are able to carry it out successfully and in an integrated way. This ensures the reformation and development of the educational system in Egypt.